2003
DOI: 10.1016/s1071-55760300004-2
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Profile of Leiomyoma and Myometrium and the Effect of Gonadotropin Releasing Hormone Analogue Therapy

Abstract: Microarray analysis allowed us to identify the profile expression of several specific genes in leiomyoma and myometrium whose expression appears to be differentially regulated after GnRHa therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(13 citation statements)
references
References 46 publications
3
10
0
Order By: Relevance
“…We also observed some changes that contradicted previous results. For example fibronectin 1, which in our study was significantly upregulated in fibroids with four independent probe sets, has been reported as downregulated in fibroids in a microarray study containing only six fibroid samples (Chegini et al, 2003). The changes in the expression profiles observed between normal myometrium and fibroid tissue also confirmed some previously reported results (Kovacs et al, 2001;Tsibris et al, 2002;Ahn et al, 2003;Chegini et al, 2003;Wang et al, 2003;Weston et al, 2003).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We also observed some changes that contradicted previous results. For example fibronectin 1, which in our study was significantly upregulated in fibroids with four independent probe sets, has been reported as downregulated in fibroids in a microarray study containing only six fibroid samples (Chegini et al, 2003). The changes in the expression profiles observed between normal myometrium and fibroid tissue also confirmed some previously reported results (Kovacs et al, 2001;Tsibris et al, 2002;Ahn et al, 2003;Chegini et al, 2003;Wang et al, 2003;Weston et al, 2003).…”
Section: Discussionsupporting
confidence: 91%
“…For example fibronectin 1, which in our study was significantly upregulated in fibroids with four independent probe sets, has been reported as downregulated in fibroids in a microarray study containing only six fibroid samples (Chegini et al, 2003). The changes in the expression profiles observed between normal myometrium and fibroid tissue also confirmed some previously reported results (Kovacs et al, 2001;Tsibris et al, 2002;Ahn et al, 2003;Chegini et al, 2003;Wang et al, 2003;Weston et al, 2003). For example, CCND1, endothelin receptor type A (EDNRA), collagen type III alpha 1 (COL3A1), and collagen type IV alpha 2 (COL4A2) were upregulated, and early growth response 1 (EGR1), complement component 1r (C1R), actin binding LIM protein 1 (ABLIM1), v-jun sarcoma virus 17 oncogene homolog (JUN), and B-cell CLL/lymphoma 6 (BCL6) were downregulated in fibroids.…”
Section: Discussionsupporting
confidence: 91%
“…Gene array studies have been conducted to clarify the alteration of gene expression profiles in uterine leiomyoma and have identified numerous genes for which expression is up-or down-regulated compared with levels in normal myometrium (Tsibris et al 2002, Catherino et al 2003, Chegini et al 2003, Skubitz & Skubitz 2003, Wang et al 2003, Weston et al 2003, Hoffman et al 2004, Quade et al 2004. Although the total number of genes analyzed in each array has varied, 5-358 genes per study have been identified as down-regulated in leiomyoma, greatly exceeding the number of up-regulated genes in eight out of nine independent array-based studies (Tsibris et al 2002, Ahn et al 2003, Catherino et al 2003, Chegini et al 2003, Skubitz & Skubitz 2003, Wang et al 2003, Weston et al 2003, Quade et al 2004, Arslan et al 2005.…”
Section: Introductionmentioning
confidence: 99%
“…Genomic microarrays have offered novel insights into the pathogenesis of these highly prevalent tumors (1)(2)(3)(4)(5) and have demonstrated both over-and underexpression of numerous genes not previously associated with leiomyomas. Using an Affymetrix U133 platform, (Affymetrix, Santa Clara, CA) our laboratory has noted that genes associated with formation of the extracellular matrix were differentially expressed in the array results (6).…”
Section: Introductionmentioning
confidence: 99%